Glycine alters the sequential pattern of swallowing activity in juvenile rat working heart–brainstem preparations - Tetsuya Seikai; Tadashi Yamanishi; Takeshi Harada; Yudai Ono; Tadataka Tsuji; Takahide Kondo; Takahiro Nishio; Yusuke Yokota; Koji Ishihama; Akifumi Enomoto; Takeshi Togawa; Susumu Tanaka; et al. (Brain Research Bulletin)
Swallowing is a centrally programmed intricate activity modulated by both excitatory and inhibitory neural transmissions to ensure that aspiration does not occur. However, the role of inhibitory transmission in swallowing is not clearly understood. The working heart–brainstem preparation (WHBP) has recently gained attention as a tool for studying the central mechanisms of swallowing. Nevertheless, the swallowing activity elicited from the WHBP has not been adequately validated. Therefore, we aimed to confirm whether the neuronal activity elicited from the WHBP represented authentic swallowing activity and to investigate the roles of inhibitory neurotransmitter receptors in the development of sequential swallowing. By applying electrical stimulation to the superior laryngeal nerve of the WHBP, sequential muscle activity was recorded from multiple muscles, from the oral cavity toward the oesophagus. This activity transported the staining solution administered through the oral cavity to the lower end of the oesophagus, confirming the activity elicited from the WHBP as swallowing activity. Additionally, we found that administering a glycine receptor antagonist accelerated the timing of activation of the middle pharyngeal constrictor muscle during sequential swallowing activity, whereas the administration of a GABAA receptor antagonist had no effect. In conclusion, we validated that the WHBP elicits swallowing activity upon electrical stimulation of the superior laryngeal nerve, and that glycine receptors contribute to the orchestration of the sequential swallowing activity.